Answer:
Step-by-step explanation:
Use quadratic formula:
x=((-b+-sqrt(b^2-4ac))/2a
x=((-9+-sqrt(9^2-4(2)(4))/2(2)
x=((-9+-sqrt(81-32))/4
x=((-9+-sqrt(49))/4
x=(-9+-7)/4
Solution 1:
x=-2/4
x=-1/2
Solution 2:
x=-16/4
x=-4
Now we check:
2(-1/2)^2+9(-1/2)+4=2/4+-9/2+4=1/2+-9/2+4=-8/2+4=-4+4=0 (x=-1/2 works)
2(-4)^2+9(-4)+4=2(16)+(-36)+4=32-36+4=-4+4=0 (x=-4 works)
So the solutions of the equation are x=-1/2 and x=-4
in this case
a=2 b=9 c4
for this equation we have the formula
x1/2 = (-b +- (root of) b2 -4ac) /2a
x1/2 = (-9 +- (root of) 81- 4×2×4)/2×2
x1/2= (-9 +- (root of) 81-32)/4
x1/2 = (-9 +- (root of) 49/4
x1/2 = (-9 +- 7)/4
x1= -9+7/4
x1=-2/4
x1=-1/2
x2= -9-7/4
x2= -16/4
x2= -4
Option D:
Difference between g(x) and f(x) is 44.
Solution:
Let us first write the function of f(x).
Take any two points on the line (0, -1) and (-2, 0).
Here,
Equation of a line:
Do cross multiplication.
-2(y + 1) = x
-2y - 2 = x
Add 2 on both sides.
-2y = x + 2
Divide by -2 on both sides.
y = -0.5x - 1
f(x) = -0.5x - 1
At x = 20,
f(20) = -0.5(20) - 1 = -11
g(x) = 1.5x + 3
g(20) = 1.5(20) + 3 = 33
Difference between g(x) and f(x)
= g(20) - f(20)
= 33 - (-11)
= 33 + 11
= 44
Difference between g(x) and f(x) is 44.
Option D is the correct answer.
Hello,
If this is the case, i would division.
4 devided by 5 is 1 reminder 1.
Plz mark brainliest
*i think i got it right!*
Answer:
212
Step-by-step explanation:
They needed 212 gallon cans
Answer: each student will receive 2 pounds
Step-by-step explanation:
Round that number to the nearest ten.
Answer: 90
Step-by-step explanation: